Prognostic significance of early acute kidney injury in COVID-19 patients requiring mechanical ventilation: a single-center retrospective analysis - Michal Sitina; Vladimir Sramek; Martin Helan; Pavel Suk (Renal Failure)
Acute kidney injury (AKI) is associated with impaired outcomes in critically ill COVID-19 patients. However, the prognostic significance of early AKI is poorly described. We aimed to determine whether AKI on admission to the intensive care unit (ICU) and its development within the first 48 h predict the need for renal replacement therapy (RRT) and increased mortality. An analysis of 372 patients with COVID-19 pneumonia requiring mechanical ventilation without advanced chronic kidney disease from 2020 to 2021 was performed. The AKI stages on ICU admission and Day 2 were determined using adapted KDIGO criteria. The early development of renal function was assessed by the change in AKI score and the Day-2/Day-0 creatinine ratio. Data were compared between three consecutive COVID-19 waves and with data before the pandemic. Both ICU and 90-day mortality (79% and 93% vs. 35% and 44%) and the need for RRT increased markedly with advanced AKI stage on ICU admission. Similarly, an early increase in AKI stage and creatinine implied highly increased mortality. RRT was associated with very high ICU and 90-day mortality (72% and 85%), even surpassing that of patients on ECMO. No difference was found between consecutive COVID-19 waves, except for a lower mortality in the patients on RRT in the last omicron wave. Mortality and need for RRT were comparable in the COVID-19 and pre-COVID-19 patients, except that RRT did not increase ICU mortality in the pre-COVID-19 era. In conclusion, we confirmed the prognostic significance of both AKI on ICU admission and its early development in patients with severe COVID-19 pneumonia.